Leaders' effects on Empowerment and Innovation - National Differences Between China, UK, and GAS in Authentic Leadership - Paul Goldmann; Vinzenz Krause; Björn Schäfer (Marketing Review St.Gallen, 2021)
Authentic leadership is a beneficial approach to transformation processes. This study examines its effects on empowerment, work engagement, and innovative performance in a multinational context (Germany/Austria/Switzerland, UK, China). There are subtle differences in its effects, but our results show the value of this leadership behavior for multinational enterprises.
Keywords: 650